SISTEM INFORMASI DAN STOK BATIK JUMPUTAN PALEMBANG(STUDI KASUS: UMKM BATIK JUMPUTAN DI KELURAHAN TUAN KENTANG, PALEMBANG) - Ridho Darmawan; Claria Dwi Saputri; Hesyah Mayusdila (Jurnal Riset Sistem Informasi, 2026)
This study aims to design and develop a web-based sales and inventory information system for Batik Jumputan MSMEs in Tuan Kentang Village, Palembang. The main problem is that transaction and inventory records are still managed manually, causing data errors and report delays. The system was developed using the Waterfall method and implemented with PHP and MySQL, and tested using Black-Box Testing. The results show that the system improves transaction recording efficiency, simplifies inventory management, and provides accurate real-time sales and inventory reports.